Shortcut - Macaulay, David (Boston : Houghton Mifflin, 1995)
Visual clues provide answers to the mysterious interrelationship of a series of brief stories.
"Walter Lorraine books"--T.p. verso.
Elem. School Library Collection.
School Library Journal starred.
Wilson's Children.
3.5
K-3
Keywords: Humorous stories; Literary recreations; Humorous fiction; Literary recreations